Current trend of radiotherapy for glioblastoma in the elderly: a survey study by the brain tumor Committee of the Korean Radiation Oncology Group (KROG 21–05). (23rd April 2022) - Wee, Chan Woo; In Yoon, Hong; Lee, Sea-Won; Lim, Do Hoon
Abstract: Background: To investigate the current variability in radiotherapy practice for elderly glioblastoma patients. Methods: A questionnaire comprising general information on elderly glioblastoma, treatment selection, radiotherapy and 16 clinical case-scenario-based questions (based on age, performance, extent of resection and MGMT promoter methylation) was sent to brain tumor radiation oncologists. Results: Twenty-one responses were recorded. Most (71.4%) stated that 70 years is an adequate cut-off for 'elderly' individuals. The most preferred hypofractionated short-course radiotherapy schedule was 40–45 Gy over 3 weeks (81.3%). The median margin for high-dose target volume was 5 mm (range, 0–20 mm) from the T1-enhancement for short-course radiotherapy. The case-scenario-based questions revealed a near-perfect consensus on 6-week standard radiotherapy plus concurrent/adjuvant temozolomide as the most appropriate adjuvant treatment in good performing patients aged 65–70 years, regardless of surgery and MGMT promoter methylation. Notably, in 75-year-old patients with good performance, the most preferred treatment was 6-week radiotherapy (81.0–90.5%) plus concurrent/adjuvant temozolomide (71.4–95.2%) rather than short-course radiotherapy or radiotherapy alone. Although the use of 3-week short-course radiotherapy increased with age and decreased performance status (all P < 0.05), 6-week radiotherapy was adopted in a significant proportion of responders (14.3–23.8%) even for wheelchair-bound, 75-year-old patients. Temozolomide use was affected by age, performance and MGMT promoter (all P < 0.05). Conclusions: A high level of consensus was observed in treating elderly glioblastoma patients with good performance status. However, the variability increased, especially for older patients and those with poor performance. This study serves as a basis for designing future clinical trials in elderly glioblastoma. Abstract : This survey study regarding the utilization of radiotherapy in elderly glioblastoma patients provides information on current practice patterns and provides basis for future clinical trials.